ANALISIS KARAKTERISTIK MINYAK TRANSFORMATOR MENGGUNAKAN PENGUJIAN DISSOLVED GAS ANALYSIS (DGA) PADA IBT 1 GARDU INDUK - Agus Siswanto; Abdul Rohman; Sugeng Suprijadi; Mudofar Baehaqi; Arifudin Arifudin (Foristek, 2022)
Electrical energy is an important factor to support people's lives. Electrical energy from the generator is channeled through a transmission line to the substation. Transformer (transformer) is a very important equipment in the electric power system. Inside there is oil which functions as an insulating medium and also as a cooling medium. This electrical and thermal load can cause dissolved gases in the transformer oil. This DGA (Dissolved Gas Analysis) test aims to determine the content of dissolved gases in transformer oil and then to analyze using three fault indication methods Total Dissolved Combustible Gas (TDCG) Method, Roger Ratio, and Duval Triangle. Results The analysis uses these three methods to determine corrective actions according to the condition of the transformer oil. Corrective action to return the dissolved gases in the transformer oil back to normal. Transformer oil filtering aims to remove or reduce potentially damaging gases from the transformer oil content. On December 29, 2020 the transformer experienced an increase in the content of flammable hydrogen gas and acetylene gas, the TDCG value was 1520 ppm and after corrective action the dissolved gas content decreased to 481 ppm, so that the condition of the transformer oil returned to normal.